The Role of Current Techniques and Concepts in Peripheral Nerve Repair. (20th January 2016) - Houschyar, K. S.; Momeni, A.; Pyles, M. N.; Cha, J. Y.; Maan, Z. N.; Duscher, D.; Jew, O. S.; Siemers, F.; Schoonhoven, J. van
Abstract : Patients with peripheral nerve injuries, especially severe injury, often face poor nerve regeneration and incomplete functional recovery, even after surgical nerve repair. This review summarizes treatment options of peripheral nerve injuries with current techniques and concepts and reviews developments in research and clinical application of these therapies.